Notes on the genus Leptostrangalia Nakane & Ohbayashi, 1959 (Coleoptera: Cerambycidae: Lepturinae: Lepturini) with description of a new species from Damingshan, Guangxi, south China - Huang, Jianhua; Vives, Eduard (Zootaxa, 2019)
Taxonomic notes on the lepturine genus Leptostrangalia Nakane & Ohbayashi, 1959 are provided and a new species from China, Leptostrangalia rufithorax nov. sp., is described. A key to the world species of the genus is provided.